Officiële Belgische Stripcatalogus deel 1. - Dewilde, Danny (Gent : 9de Kunst Grafiek Galerij, 1997)
Berck (Berckmans, Arthur) ; De Bie, Erwin ; Bosschaert, Jan ; Broeckx, Jef ; Buth (Budt, Leo De) ; Carrie, Anne ; Cis (Verhammen, Cis) ; Claerhout, May (Mario) ; Clement, Rik ; Confusius, Pjotr (Rijcker, Piet De) ; De Coninck, Jeroen ; Cram (Mestag, Marc) ; Declercq, Gilbert ; Dejaegere, André ; Demoen, Renaat ; Dhondt, Steven ; Dupré, Steven ; Eembeek, F. ; Ewé (Wouters, Edwin) ; Fabri, Leo ; Gastmans, Edgard ; Geerts, Paul ; Geets, Willy ; Gijbels, Luc ; Goelen, Werner (Griffo) ; Got (Timmermans, Gommaar) ; Gray (Croucher) ; Herckens, Stefaan ; Herr Seele ; Heuvel, Fritz Van Den ; Hugoke (Kempeneer, Hugo De) ; Hurey (Reymaeker, Hugo De) ; Ikke (Legendre, Marc) ; Jean-Pol (Vandenbroeck, Jean-Pol) ; Kabou (Boumans, Karel) ; Kamagurka ; Kinnaert, Geert ; Leemans, Hector ; Linthout, Willy ; Lusse ; Mahy, Michel ; Marvano (Oppen, Mark Van) ; Mau, Bob ; Meersman, Hugo ; Merho (Merhottein, Robert) ; Mertens, Willy ; Meynen, Erik ; Michiels, Dirk ; Moerman, Lukas ; De Moor, Bob ; Morjeau, Luc ; Morris (Bevere, Maurice De) ; Musschoot, Mark ; Nagel (Nagels, Edwin) ; Nys, Jef ; Pavali (Lierde, Patrick Van) ; Peeters, Wouter ; Pink (Hermans, Eugeen) ; Pirana (Velde, Leon Van De) ; Polfliet, Sylvain ; Pom (Hove, Jozef Van) ; Van Raemdonck, Georges ; Raven, Erika ; De Rie, Steven ; Van Riet, Jean ; Van Riet, Ronald ; de Rijcker), ERik Meynen en Pjotr Confusius (Piet ; Rik (Jottier, G.) ; Roderyck (Ruyck, Roger De) ; De Rop, Edward ; De Rop, Eric ; Ryssack, Eddy ; Schatteman, Lieve (Lie) ; Sels, Erwin ; Sels, Frank ; Sinap (Panis A.) ; Sleen, Marc ; Stallaert, Dirk ; Steurbaut, Marcel ; Strzelecki, Caryl ; Taymans, Henri (Timme) ; Tibos, Piet ; Tuerlinckx, Stefaan ; Valcke, Fred ; Vance (Cutsem, William Van) ; Vandemeulebroecke, Eric ; Vandersteen, Willy ; etc.
boek